Lacrimal Gland Hypoplasia and Corneal Anesthesia in MIRAGE Syndrome: A Case Report and Literature Review. Issue 8 (22nd August 2022) - Basilious, Amy; Basilious, Alfred; ElJalbout, Ramy; Robert, Marie-Claude
Abstract : Purpose: The purpose of this report was to describe the ocular findings in Myelodysplasia, Infection, Restriction of growth, Adrenal hypoplasia, Genital problems, and Enteropathy (MIRAGE) syndrome, a multisystem congenital disorder. Methods: This was a case report and literature review. Results: An infant with MIRAGE syndrome (combined immunodeficiency with recurrent infections, growth restriction, adrenal insufficiency, 46, XY karyotype with hypovirilization, dysphagia, gastroesophageal reflux disease, and dysautonomia) underwent ophthalmological evaluation because of persistent conjunctivitis during his 8-month admission in the neonatal intensive care unit. His parents noted absence of tears when crying since birth. Bilateral broad corneal epithelial defects were noted, and treatment was initiated with frequent lubricating ointment. At 9 months, his vision was estimated at 20/380 in both eyes using Teller Acuity Cards. There were persistent bilateral epithelial defects, confluent punctate epithelial erosions, low Schirmer strip wetting (right eye 3 mm and left eye 2 mm), and decreased corneal sensation. Brain magnetic resonance imaging images demonstrated hypoplastic lacrimal glands bilaterally. More aggressive lubrication and installation of punctal plugs in all 4 lids were successful at preventing further epithelial defects. Conclusions: This case presents deficient lacrimation as a manifestation of MIRAGE syndrome and is the first to identify lacrimal gland hypoplasia and corneal anesthesia. Autonomic and neurologic dysfunction have been proposed to play a role in the pathophysiology of hypolacrimation in similar syndromes and likely contributed to the poor ocular surface in this case. Patients with MIRAGE should undergo ophthalmic assessment as soon as possible after birth because early intervention is essential to preventing irreversible corneal damage.